The body dissatisfaction role in the adoption of compulsive healthy eating behaviors - Silva, Susana C. (2023)
This study investigates the effect of Instagram use, fitness and health-related content, internalization, social comparisons, perfectionism, and obsessive-compulsive personality traits on body dissatisfaction and Orthorexia Nervosa. Moreover, the study discusses the differences between Portuguese and Brazilian societies to underline the potential role of cultural dimensions. A survey-based study with a sample of 238 respondents has been developed to test the proposed model using structural equation modelling. The data analysis shows that the main factors influencing body dissatisfaction and Orthorexia Nervosa are internalizing beauty ideals, social comparisons (both upward and downward), and perfectionism. Body dissatisfaction mediates the path from internalization, upward and downward comparisons, perfectionism from one side, and Orthorexia Nervosa on the other. Finally, results from Portuguese and Brazilian samples were similar revealing no significant role of cultural differences. Based on the findings, the study concludes by discussing the theoretical contributions and providing actionable managerial implications.